Derivation in Functional Discourse Grammar: Some challenges and implications. (March 2018) - Keizer, Evelien
Abstract : One distinctive feature of Functional Discourse Grammar (FDG) is that it distinguishes two types of derivational processes: Lexical derivation, which takes place in the lexicon, and syntactic derivation, which takes place in the grammar. The aim of this paper is to consider some of the implications of this approach by addressing three major issues: i) on the basis of which criteria do we decide which derivational processes are lexical and which are syntactic, ii) how does the FDG approach deal with recursive processes of derivation, and iii) how do these two derivational processes interact with other types of word formation, such as compounding, conversion and back-formation.